Immediate hypersensitivity to marine snail (cerithidea obtusa) allergen among local patients with atopic diseases - Salahudin Abd Aziz Norazlin, Misnan Rosmilah, Mohamad Yadzir Zailatul Hani, Bakhtiar Faizal, Abdullah Noormalin, Murad Shahnaz, (Universiti Pendidikan Sultan Idris, 2016)
Immediate hypersensitivity to marine snail (cerithidea obtusa) allergen among local patients with atopic diseases by Salahudin Abd Aziz Norazlin, Misnan Rosmilah, Mohamad Yadzir Zailatul Hani, Bakhtiar Faizal, Abdullah Noormalin, Murad Shahnaz,